Personalized Politics, Presidentialized Systems, and Migration - Malass, Jad (2022)
This thesis investigates the relationship between migration policies followed by governments and the characteristics and nature of “personalized politics” at the executive level of government. It focuses mainly on decisions that involve migrations issues at international borders since 2016, and precisely on issues on the southeast of the European Union’s border. It lends credence to the argument that there is a direct correlation between the nature and the level of personalized politics at the executive level and the migration policies followed by states. As argued in the thesis, “personalized politics” is the outcome of the personality of the political executive (president or prime minister) and the political powers granted to him/her by his/her country’s constitution and political system. The thesis employs the comparative multi-case study research design, combining components of both cross-sectional and case study designs. It investigates the cases of the former German Chancellor Angela Merkel and Turkish President Recep Tayyip Erdogan in the context of the EU-Turkey statement on migration governance. After employing a Leadership Trait Analysis (LTA) with a comparison of executive power allocations between the two cases, the thesis concludes that leadership traits directly affected the nature of border policies between Turkey, Germany, and EU.